Mechanical vs. electrical hysteresis of carbon nanotube/styrene-butadiene-styrene composites and their influence in the electromechanical response - Costa, P. (2015)
The interesting properties of thermoplastics elastomers can be combined with carbon nanotubes (CNT) for the development of large strain piezoresistive composites for sensor applications. Piezoresistive properties of the composites depend on CNT content, with the gauge factor increasing for concentrations around the percolation threshold, mechanical and electrical hysteresis. The SBS copolymer composition (butadiene/styrene ratio) influences the mechanical and electrical hysteresis of composites and, therefore, the piezoresistive response. This work reports on the electrical and mechanical response of CNT/SBS composites with 4%wt nanofiller content, due to the larger electromechanical response. C401 and C540 SBS copolymers with 80% and 60% butadiene content, respectively have been selected. The copolymer with larger amount of soft phase (C401) shows a rubber-like mechanical behavior, with mechanical hysteresis increasing linearly with strain until 100% strain. The copolymer with the larger amount of hard phase (C540) just shows rubber-like behavior for low strains. The piezoresistive sensibility is similar for both composites for low strains, with a GF≈ 5 for 5% strain. The electrical hysteresis shows opposite behavior than the mechanical hysteresis, increasing with strain for both composites, but with higher increase for softer copolymer, C401. The GF increases with increasing strain, but this increase is larger for composites with lower amounts of soft phase due to the distinct initial modulus and deformation of the soft and hard phases of the copolymer. The soft phase shows larger strain under a given stress than the harder phase and the conductive pathway rearrangements in the composites are different for both phases, the harder copolymer (C540) showing higher piezoresistive sensibility, GF≈ 18, for 20% strain.